2 - Why Nigerian agbada fabric is (often) imported, while Indian sari fabric is local: a comparative history of textile manufacturing - Kamara, Yarri B. (Africa Development, 2023)
In the 1980s, both India and Nigeria had textile sectors that satisfied their large domestic demand. Today, however, Nigeria imports most of its textiles, including identity-imbued fabrics, while India is a major textiles producer. This article proposes three explanatory factors for this divergence based on a review of secondary sources. From independence, Indian policy placed greater emphasis on supporting craft and small-scale textile production, whereas the craft sector in Nigeria was neglected. Nigeria’s indigenisation of industry strategies failed to achieve endogenous processes in the textile industry, whereas the Indian textile sector was characterised by high Indian ownership and endogenous skills and technologies that rendered the sector resilient to shocks. Lastly, while both countries adopted import-substituting industrialisation strategies, the Nigerian textile sector benefited from little trade protection as smuggling greatly undermined the protection in place.